ANXIETY, DEPRESSION AND QUALITY OF LIFE IN PATIENTS WITH GLAUCOMA - Tošić Golubović, Suzana; Jocić, Hristina; Gugleta, Uroš; Nikolić, Gordana; Stojanović, Nikola M (Acta medicae Medianae, 2022)
Previous studies have shown significant comorbidity between depressive, anxious disorders, and glaucoma, which is the second most common cause of vision loss in the world. This study aimed to determine the presence of depression and anxiety, assess of the quality of life in patients with glaucoma, as well as to compare with the results of the healthy population. Cross-sectional study, was carried out at the Ophthalmology Clinic, of the University Clinical Center Niš. The presence of anxiety, and depression, were evaluated by Zung’s self-rating instruments for anxiety, and depression, and the quality of life was evaluated by the WHO Quality of life instrument-Brief version. Sociodemographic and glaucoma-related parameters were gathered. Around 38.64% of patients with glaucoma presented depression, mostly mild and moderate forms, while mild depression was found in 4.17% of respondents in the control group. The number of patients with anxiety was two times higher in the experimental than in the control group. Mentioned results show a statistically relevant difference (p < 0.01). We determined a statistically relevant correlation between the frequency of depression and the severity of glaucoma (p < 0.001), while no such correlation was found between anxiety and the severity of glaucoma (p > 0.05). While comparing the gathered values for each domain as well as the overall QOL we found a statistically relevant difference (p < 0.001). A statistically relevant correlation was found between the patients with milder and more severe glaucoma forms. Comorbid depression and anxiety in patients with glaucoma occur in more severe forms of glaucoma, in patients with a longer duration of the disease for medical and psycho-social reasons.